Power Efficiency Evaluation of Low-Cost IoT Repeater in Indoor Wireless Networks: Politeknik Aceh Selatan Campus Case Study - Erwinsyah Sipahutar; Alfi Hafizh; Rial Fauza; Rudi Arif Candra (Politeknik Aceh Selatan, 2025)
Low-cost Wi-Fi repeaters are increasingly deployed in smart campus environments to enhance indoor wireless coverage; however, their energy performance under realistic traffic conditions remains insufficiently quantified. This paper presents a comprehensive experimental evaluation of the power efficiency of an ESP8266-based IoT repeater operating in simultaneous Access Point and Station (AP+STA) mode over IEEE 802.11n (2.4 GHz). Unlike prior studies focusing primarily on protocol-level optimization or simulation-based relay models, this work provides hardware-level, real-time power characterization under controlled multi-client traffic scenarios. Experimental measurements demonstrate that average power consumption increases from 0.26 W (78 mA) in idle mode to 0.60 W (182 mA) with a single active client and up to 0.87 W (264 mA) under five-client high-load conditions. The maximum observed throughput reaches 18.4 Mbps, while energy per transmitted bit degrades from 0.032 µJ/bit to 0.047 µJ/bit as traffic intensity increases, revealing a measurable efficiency loss due to simultaneous packet reception and retransmission. A near-linear correlation (R² > 0.94) between traffic load and power consumption is identified, enabling the derivation of an empirical energy–performance model. The findings provide quantitative insight into the trade-off between coverage extension and energy demand in low-cost IoT repeaters. The proposed evaluation framework and empirical model support energy-aware deployment strategies for smart campus